Prospects for the global helium industry development. (June 2022) - Provornaya, I.V.; Filimonova, I.V.; Eder, L.V.; Nemov, V.Y.; Zemnukhova, E.A.
Abstract: The article is devoted to a comprehensive analysis of the global helium industry. The areas of efficient use of associated components in natural gas production are an integral part of the technological economy. The article discusses the current state of the world production and consumption of helium. Russia possesses the largest reserves of helium in the world, most of which are concentrated in the fields of Eastern Siberia and the Far East. Russia can become the main producer and supplier of helium to the world market. The paper also analyzes the current state of the production and consumption of helium in the world with the identification of the main helium producers (USA, Qatar, and Algeria). The main factors influencing the production and consumption of helium have been determined. The authors have constructed a forecast for the production and consumption of helium in the world until 2040 according to three scenarios. An assessment was made of the possibility of transporting helium from Russia to the world market until 2040. In addition, the authors considered options for creating storage facilities for helium concentrate on the territory of Eastern Siberia.